The Estimation of Generalized Method Moment Poisson Regression Model on the Prevalence of Acute Respiratory Tract Infection (RTI) in South Kalimantan - Mahpolah Mahpolah; Suharto Suharto; Arief Wibowo; Bambang Widjanarko Otok (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
ACUTE (RTI) is still an important health problem because the cause of the death of infants and children under five high enough, 1 from 4 death that happens. The purpose of this research examines the factors that affect the genesis ACUTE (RTI) using poisson regression approach with estimates of the maximum likelihood estimator (MLE) and generalized method moment (GMM). This research done in the area of Health Clinic in South Kalimantan. The results of the study showed that the estimates of the GMM method on Poisson regression model gives better performance in terms of the significance of the parameters than the MLE method. The factors that affect an increasing number of the prevalence of ACUTE (RTI) a region namely persentase Breast Feeding non-exclusive (0.0279), the percentage of low birth weight (0.0569), the percentage of shelter density (0.028), the percentage of the existence of smoker family members in the house (0.0308), the percentage of immunization is not complete (0.0193). While the factors that affect a downturn in the number of the prevalence of ACUTE (RTI) in a region which is the percentage of the number of infants less than 2 (0.0364), the percentage of normal nutrition status (0.0224), the percentage of Mothers Education on high school (0.0339), and the percentage of social economy (UMP enough to top) (0.0194).